Simulation and Optimization of Emitter Thickness for Indium Arsenide-Based Thermophotovoltaic Cell - Wong B.W.A.; Gamel M.M.A.; Lee H.J.; Rashid W.E.; Yao L.K.; Jern K.P. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cells; Cytology; Efficiency; III-V semiconductors; Indium; Infrared radiation; Nanoelectronics; Narrow band gap semiconductors; Open circuit voltage; Electrical characteristic; III-IV semiconductors; InAs; Silvaco; Simulation and optimization; Thermophoto voltaic cells; Thermophotovoltaic devices; Thickness; Indium arsenide